Fundamental formulation for frictional contact problems of coated systems - Ma, L; Korsunsky, A (Elsevier, 2004)
The plane problem about surface loading of an elastic layer perfectly bonded to an elastically dissimilar half-plane is considered. The fundamental solutions for concentrated forces acting perpendicular and parallel to the layer surface are obtained. The stress and displacement fields in the coating layer and the substrate due to these concentrated forces are found. On the basis of these expressions, the fundamental integral equations are obtained which describe the frictional contact between an elastic body and a coated substrate. From the fundamental integral equations, a series of integral equations for special cases are deduced corresponding to practical contact situations. Finally, the numerical results for a typical example are given to demonstrate the validity of the fundamental equations and numerical procedures given in this paper.